Development of Flipbook-Based PAI Teaching Modules for Class 1 SDN Tlontoraja 1 Pasean District, Pamekasan Regency - Maszeri; Novia Wulandari; Nurul Zainab (STIT Attaqwa, 2024)
This research aims to find out 1) the process of developing flipbook-based teaching modules on the sub-theme of the story of the Prophet Adam as the first human on earth in class 1 SD/MI; 2) Effectiveness in applying flipbook-based teaching modules to the sub-theme of the Prophet Adam's story as the first human on earth in class 1 SD/MI. This type of research is design and product development (Design and Development) research with reference to the ADDIE model used to develop flipbook-based teaching modules, namely Fliphtml.com, user validity is measured using expert tests which include media experts, material experts and linguists. The data that has been collected is then converted using a likert scale. User responses were obtained from respondents, namely 1 teacher and 20 grade 1 students. The research results show that 1) validity tests are media experts, material experts and linguists. The overall average of validation was 90.56% which was at the interval 81%-100% which shows that it is in the very valid category. 2) the average response of teachers and students to teaching modules was 85.15% at the interval 81%-100% with the category being very practical. Based on these results, it was concluded that this study produced valid and practical teaching materials.